Taxonomic and functional shifts in stream macroinvertebrates associated with riparian cover in tropical dry forests - Cuellar-Cardozo, José A. (2026)
Introduction: Lotic systems exhibit characteristics defined by their interactions with the surrounding areas. Riparian forests and water flow are fundamental elements for the maintenance of macroinvertebrate diversity. Therefore, it is essential for preservation of these functions, especially in threatened environments such as dry tropical forests. Objective: To evaluate the relationship between riparian forest quality, water physicochemical variables, and the taxonomic and functional diversity of macroinvertebrates associated with leaf litter. Methods: In a stream draining tropical dry forest, we sampled macroinvertebrate communities using leaf traps, in sites with different conditions of riparian forest, along with leaf litter inputs for each site, during a year. We performed PERMANOVA to compare treatments and factors, and used Multiple Linear Regression Model and Redundancy Analysis to associate environmental variables with changes in taxonomic and functional diversity. Results: Conserved riparian forests have an effect on functionality, positively related to higher functional richness and traits like functional feeding group variety and bigger head width. Meanwhile, functional distance and functional evenness are not related to Qualitat del Bosc de Ribera index (QBR) in the stream. Also, changes in vertical and drifting leaf litter input, coupled with increased total dissolved solids due to runoff, alter stream conditions sufficiently to generate community changes and decreases in abundance, correlated with areas of lower QBR therefore less tree canopy cover and higher solar radiation. Conclusions: We found that riparian forest quality and environmental variables like total dissolved solids and solar radiation influence the taxonomic and functional diversity of macroinvertebrates.